The Phenomena of Curriculum Development and Shifting in Modern Era - Gressya Pebriani Agatha Tamba; Chesia Aulia; Jauharotun Ramadhani Ahmad; Kristi Debora Siagian; Winda Valerina Simanjuntak; Natalia Silalahi (International Journal of Educational Practice and Policy, 2024)
This research discusses the development and shifting of curriculum in the modern era, highlighting the changing paradigm of education to address global needs and local challenges. The study traces the evolution of the curriculum, from traditional concepts to modern innovations such as the Merdeka Curriculum. Particular attention is paid to the integration of project-based approaches, learning flexibility and strengthening student character through the values of the Pancasila Student Profile. It also reviews the drivers and inhibitors of curriculum development, including teacher readiness, educational infrastructure, and social and cultural dynamics. Policy implications show the importance of collaboration between government, educators and communities to ensure the successful implementation of a relevant, inclusive and adaptive curriculum. This research offers strategic recommendations to build an education system that is able to respond to the demands of the digital era and the diversity of society